Effect of Storage Period on the Fermentation Profile and Bacterial Community of Silage Prepared with Alfalfa, Whole-Plant Corn and Their Mixture - Kai Mao; Zhu Yu; Shuai Huang; Musen Wang; David B. Hannaway (Fermentation, 2022)
This study aimed to investigate the impact of storage time on the bacterial community and fermentation profile of silage prepared with alfalfa, whole-plant corn, and their mixture. Fresh alfalfa and whole-plant corn were chopped and combined in fresh weight ratios of 1:0 (alfalfa, control), 0.8:0.2 (M1), 0.6:0.4 (M2), and 0:1 (corn). Three silos of each treatment were analyzed after 30, 60, and 90 d of storage. With storage time, pH, acetic acid, propionic acid, butyric acid, and ammonia nitrogen levels increased in alfalfa silage (p < 0.01), whereas lactic acid level decreased (p < 0.01). Compared to alfalfa silage, M1, M2, and corn silages were better fermented and more stable during storage. The dominant bacteria in M1, M2, and corn silages shifted significantly from L. plantarum, L. buchneri, and L. brevis to L. acetotolerans and L. buchneri during 30 to 60–90 d of storage, and storage time decreased the bacterial diversity of these silages. In conclusion, storage time significantly decreased the fermentation quality of alfalfa silage and remarkably optimized the bacterial community structure of well-fermented M1, M2, and corn silages. Alfalfa should be ensiled with at least 20% whole-plant corn to improve silage fermentation quality and storage stability.